Cardiovascular Hemodynamics for the Clinician. - Stouffer, George (John Wiley & Sons, 2008)
Now you have a dependable guide to the practical application of hemodynamics. This concise handbook will help both practicing and prospective clinicians better understand and interpret the hemodynamic data used to make specific diagnoses and monitor ongoing therapy. Written from the perspective of a clinician, this convenient paperback opens with an overview of the basics of hemodynamics, then devotes chapters to specific disease states. Topics include:. coronary artery disease. cardiomyopathies. valve disease. arrhythmias. pericardial disease. Numerous pressure tracings throughout t.